Experimental Investigation of the Effects of Helical Roof on the Performance of Stairmand High Efficiency Cyclone - Aykut Karadeniz; Selami Demir (International Journal of Chemical Engineering)
Cost-effectiveness of a standard and a modified Stairmand high-efficiency type cyclone was compared at various inlet gas velocities. The modified design was obtained by replacing the roof of the standard design with a helical roof. Experiments were conducted by both standard and helical roof designs at the same operating conditions. Results showed that helical roof leads to reduced pressure drop in cyclones while having a negative impact on particle collection efficiency. Reductions in pressure drop can reach up to 30%, while particle collection efficiency is reduced by up to 8% simultaneously. Overall, the treatment cost of a cyclone separator can be reduced by 14.1–20.8%. Results indicated that helical roof design cyclones can be used to reduce overall treatment cost by cyclone separators.